In situ observation of reactive oxygen species forming on oxygen-evolving iridium surfaces. Issue 3 (8th December 2016) - Pfeifer, Verena; Jones, Travis E.; Velasco Vélez, Juan J.; Arrigo, Rosa; Piccinin, Simone; Hävecker, Michael; Knop-Gericke, Axel; Schlögl, Robert
Abstract : In situ XAS measurements reveal that electron-deficient oxygen species form during OER on IrOx and correlate with catalytic activity. Abstract : Water splitting performed in acidic media relies on the exceptional performance of iridium-based materials to catalyze the oxygen evolution reaction (OER). In the present work, we use in situ X-ray photoemission and absorption spectroscopy to resolve the long-standing debate about surface species present in iridium-based catalysts during the OER. We find that the surface of an initially metallic iridium model electrode converts into a mixed-valent, conductive iridium oxide matrix during the OER, which contains O II− and electrophilic O I− species. We observe a positive correlation between the O I− concentration and the evolved oxygen, suggesting that these electrophilic oxygen sites may be involved in catalyzing the OER. We can understand this observation by analogy with photosystem II; their electrophilicity renders the O I− species active in O–O bond formation, i.e. the likely potential- and rate-determining step of the OER. The ability of amorphous iridium oxyhydroxides to easily host such reactive, electrophilic species can explain their superior performance when compared to plain iridium metal or crystalline rutile-type IrO2 .